Design Monitoring and Automatic Control System for Modern Chicken Cage - Mudofar Baehaqi; Yepie Dwi Vaktiyan; Arifudin Arifudin; Agus Siswanto (Mestro, 2022)
Automatic monitoring and control technology in chicken coops can be useful for broiler breeders in carrying out their daily farming activities. Monitoring data on environmental conditions in the cage can be done remotely with the help of the internet, as well as automatic control to maintain the stability of ideal conditions in the cage can be controlled based on the reading value of the current condition of the cage. The purpose of this research is to make it easier for breeders to carry out monitoring activities and regulate the stability of environmental conditions in the cage automatically with the help of internet of things technology. The stages of the research carried out were designing a chicken coop prototype and conducting control trials based on sensor reading values and designing a website for real-time data monitoring interfaces. The data obtained from this study were in the form of temperature, humidity and ammonia values in the cage. The research results for data monitoring show changing values during one week of monitoring. With this research, if it is further developed, it is hoped that it can regulate the ideal environmental conditions of the coop so that it can be maintained and the growth of the chickens can be more optimal.